In-office Bleaching Activated With Violet LED: Effect on Pulpal and Tooth Temperature and Pulp Viability - Carlos, N. R.; Basting, R. T.; Kantovitz, K. R.; Bronze-Uhle, E. S. [UNESP]; Lisboa Filho, P. N. [UNESP]; Cavalli, V. (My University, 2024)
OBJECTIVES: This study evaluated the influence of hydrogen peroxide (HP) with or without titanium dioxide nanotubes (TiO2) associated with violet LED (VL) regarding: a) the temperature change in the pulp chamber and facial surface; b) the decomposition of HP; and c) the cytotoxicity of the gels on pulp cells. METHODS AND MATERIALS: The experimental groups were: HP35 (35% HP/Whiteness HP, FGM); HP35+VL; HP35T (HP35+TiO2); HP35T+VL; HP7 (7.5% HP/White Class 7.5%, FGM); HP7+VL; HP7T (HP7+TiO2); and HP7T+VL. TiO2 was incorporated into the bleaching gels at 1%. Eighty bovine incisors were evaluated to determine temperature change in 8 experimental groups (n=10/group). A k-type thermocouple was used to evaluate the temperatures of the facial surface and in the pulp chamber, achieved by enabling endodontic access to the palatal surface, throughout the 30-minute session. HP decomposition (n=3) of gels was evaluated by using an automatic potentiometric titrator at the initial and 30-minute time points. Trans-enamel and trans-dentinal cell viability were assessed with a pulp chamber device as well as enamel and dentin discs (n=6), and the treatment extracts (culture medium + diffused components) were collected and applied to MDPC-23 odontoblast cells to evaluate cell viability according to the MTT test. RESULTS: A temperature increase in the pulp chamber was observed in the presence of VL at 30 minutes (p<0.05) (Mann-Whitney test). Also at 30 minutes, HP35 showed greater decomposition in the presence of VL rather than in its absence (p<0.05) (mixed linear models and the Tukey-Kramer test). HP7 provided greater cell viability than the groups treated with HP35 (p<0.05) (generalized linear models test). Cell viability was significantly lower for HP7 in the presence of VL (p<0.05). CONCLUSION: Pulpal temperature increased with VL (maximum of 1.9°C), but did not exceed the critical limit to cause pulp damage. Less concentrated HP resulted in higher cell viability, even when associated with VL.